Oyu Tolgoi Hugo North Lift 1 update: Panel 0 performance and the commencement of Panel 2 - Hanani, S; Stegman, C; Chuluunbaatar, A; Ganzorigt, T; Herselman, S; Rodda, B; McKellar, A (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
The underground operation at the Oyu Tolgoi mine in Mongolia continues to advance with construction completion of Panel 0 block cave, the first of 4 block cave mines that comprise the Hugo North Lift 1 (HNL1) orebody extraction. The 4 block caves are Panel 0 (P0), Panel 2 North (P2N), Panel 2 South (P2S) and Panel 1 (P1). This marks a significant milestone in the ramp-up of one of the world’s largest block caving projects. P0 began its journey with the first undercut blast and first drawbell blast in January and June 2022, respectively. The extraction level construction was completed in October 2024, delivering 124 drawbells and 229 drawpoints, whilst also achieving a maximum drawbelling construction rate of 6 drawbells per month for 10 consecutive months. Current production is exceeding its nameplate capacity of 30 ktpd by upwards of 10%. Building on this success and the extensive lessons gained during the construction and rampup phases, P2N commenced its first undercut blast in April 2025 and achieved its first drawbell in August 2025 – also ahead of plan. P0’s development, construction and caving phases are shaping the future of Oyu Tolgoi’s underground expansion. Lessons from critical infrastructure readiness, design optimisation, critical path management, undercut quality control and cave health monitoring all form part of the continuous improvement journey for the subsequent panels. Together, they set the stage for early and sustained copper production with a maximised reserve recovery, laying the foundation for the future caves at Oyu Tolgoi.
Keywords: block cave; ramp-up; performance; critical path; caving